Recurrent Indeterminate Dendritic Cell Tumor of the Skin - Jin Woo Joo; Taek Chung; Yoon Ah Cho; Sang Kyum Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Indeterminate dendritic cell tumor (IDCT) is a dendritic cell tumor that displays histologic features similar to those of Langerhans cells. The origin of the indeterminate cells may represent precursors of Langerhans cells or skin dendritic cells. IDCT is extremely rare, and tumor progression and predictive factors are not well known. Here, we report a case of a 61-year-old man who presented with a papule on his back and was finally diagnosed with IDCT based on histology and immunohistochemistry. The tumor recurred three months after surgical excision.